Study of Nitrogen Fertilizer Concentration and Types of Growth Regulators in Vegetative Growth of Orchid Plants (Dendrobium spp) - Abdul Wachid (Universitas Muhammadiyah Sidoarjo, 2010)
This study was conducted to determine the initial growth of orchids from application of various concentrations of nitrogen and various growth regulators. The location is at the experimental study of Agronomy, Faculty of Agriculture, University of Muhammadiyah Sidoarjo at a height of 5 m. The factorial experiment arranged in a randomized block design (RBD) with three replications. The first factor is the concentration of nitrogen fertilizer consists of : without fertilizer N (N0), 0.3 g/l of water (N1), 0.6 g/l of water (N2), and 0.9 g/l of water (N3); the second factor is a growth regulator (PGR) consists of: without PGR (Z0), dekamon Z2 (Z1): ergon (Z2), and gibberellins (Z3). Penenlitian results showed: (i) there is no interaction between dose and concentration of nitrogen fertilizer plant growth regulator on all variables of plant growth, (ii) the concentration of nitrogen effect on all variables were observed, as well as PGR types, except the variable plant height, (iii) combined treatment of nitrogen fertilizer dose (0.6 g/l of water) with gibberelin provide the highest stem diameter (18.33 mm) and the highest number of leaves (7.67 strands) at the age of 105 HST.